Forging ahead: the role of resilience and reinvention in exceptional leadership in Malaysia and Indonesia - Yap Pei Shi,; Aqimi Rafuad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The role of resilience and reinvention in exceptional leadership in Malaysia and Indonesia is crucial in times of rapid change and challenges; where this article seeks to identify the concept of resilience and reinvention in leaders based in Malaysia and Indonesia, highlighting how these attributes enabled leaders to navigate uncertainty confidently by drawing from past experiences. This article encouraged aspiring and current leaders to adopt the principles of resilience and reinvention as guiding beacons on their journey toward leadership excellence. Furthermore, the researchers explored how exceptional leaders cultivated a culture of growth by valuing innovation, encouraging risk-taking, and promoting ongoing development. Lastly, this article suggests that a supportive environment, volunteering programs, and nation-building initiatives are the strategies to enhance resilience and reinvention in exceptional leadership among young leaders. However, with reliance on secondary data, there were limitations in data availability and finding relevant sources.